809 Comparison of Intraoperative Indocyanine Green Videoangiography Versus Postoperative Catheter Angiography to Confirm Microsurgical Occlusion of Dorsal Intradural Arteriovenous Fistulas. (1st April 2022) - Karahalios, Katherine; Srinivasan, Visish M.; Scherschinski, Lea; DiDomenico, Joseph D.; Catapano, Joshua; Safaee, Michael; Lawton, Michael T.
Abstract : INTRODUCTION: Dorsal intradural arteriovenous fistulas (DI-AVFs) represent 70% of all spinal vascular malformations and 80% of all spinal AVFs. Microsurgical clip occlusion is a durable treatment for DI-AVFs and includes pre- and postoperative digital subtraction angiography (DSA) as the standard practice. Intraoperative indocyanine green videoangiography (ICG-VA) has become a valuable intraoperative adjunct in these cases. Results with intraoperative ICG-VA have not been compared to postoperative DSA. METHODS: A multi-institutional database of vascular malformations was queried for all surgically managed cases of DI-AVFs. Patients with both intraoperative ICG-VA and postoperative DSA were included. Demographic, radiologic, intraoperative findings, and surgical outcomes data were obtained and retrospectively analyzed. RESULTS: Forty-five cases of DI-AVFs were identified. Patients had a mean age of 61.9 years old (range 26-85), including 32 males and 13 females. Except for one asymptomatic patient, all other patients presented with leg numbness and weakness, gait instability, bowel and/or bladder incontinence, back pain, paresthesias, paraplegia, upper extremity discoordination, erectile dysfunction, and/or general weakness. The majority of lesions were diagnosed in the thoracic spine (72%). All DI-AVFs were treated with interruption of the fistula with clip occlusion of the draining vein. Intraoperative ICG-VA confirmed complete obliteration in all patients. Postoperative spinal angiography was performed on 40 patients confirming complete obliteration in all patients. More patients had clinical improvement compared to their preoperative state than stayed the same (47.4% vs. 42.1%). CONCLUSIONS: ICG-VA is useful for both intraoperative identification of DI-AVFs and confirmation of complete microsurgical occlusion. Perfect correlation between intraoperative ICG-VA and postoperative DSA demonstrates the diagnostic power of the former. This finding suggests that postoperative DSA is not necessary when intraoperative ICG-VA confirms complete occlusion of the DI-AVF, which will spare patients the procedural risk and cost of this invasive procedure.